2020
DOI: 10.1007/s13238-020-00792-w
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: Novel and potent inhibitors targeting DHODH are broad-spectrum antivirals against RNA viruses including newly-emerged coronavirus SARS-CoV-2

Abstract: In the original publication there are few errors in Figure 1. The correct Figure 1 is provided in this correction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…We found that A77 1726 did not have significant antiproliferative effects when the cells were seeded in confluence and incubated for 16 h. There are several explanations: (1) in this experimental setting, the cells proliferated very slowly; (2) a small amount of uridine in the serum used for cell culture could be used for Vero cell proliferation; (3) A77 1726 does not completely shut off pyrimidine nucleotide synthesis; (4) some pyrimidine nucleotides were already present in the cells when A77 1726 was added. Consistent with our observation, Xiong et al recently reported that DHO-DH knockout does not significantly affect cell proliferation [31]. Furthermore, some tumour cell lines such as A549 cells, a cell line widely used for propagating influenza virus, almost do not express DHO-DH at all [51].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…We found that A77 1726 did not have significant antiproliferative effects when the cells were seeded in confluence and incubated for 16 h. There are several explanations: (1) in this experimental setting, the cells proliferated very slowly; (2) a small amount of uridine in the serum used for cell culture could be used for Vero cell proliferation; (3) A77 1726 does not completely shut off pyrimidine nucleotide synthesis; (4) some pyrimidine nucleotides were already present in the cells when A77 1726 was added. Consistent with our observation, Xiong et al recently reported that DHO-DH knockout does not significantly affect cell proliferation [31]. Furthermore, some tumour cell lines such as A549 cells, a cell line widely used for propagating influenza virus, almost do not express DHO-DH at all [51].…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, several prior studies have shown that DHO-DH inhibitors are not able to inhibit virus replication in vivo, although they have excellent antiviral activity in vitro [47][48][49]. In contrast, a recent study demonstrated that several potent DHO-DH-specific inhibitors are effective and even more effective than oseltamivir to inhibit influenza virus replication in vivo [31]. It appears that virus type (DNA vs RNA virus) and the genomic sequence of viruses may determine whether a DHO-DH inhibitor can control virus replication in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 7 , 8 Furthermore, lethality associated with SARS‐CoV‐2 infection has been associated with excessive activation of the immune response. 8 Emvododstat has a dual mechanism of action that inhibits SARS‐CoV‐2 replication and attenuates the production of pro‐inflammatory cytokines. 2 In vitro, cell culture assays indicate a decreased capsid protein (EC 50 1.96 nM) and decreased viral titer (EC 50 2.6 nM, EC 90 53 nM) of SARS‐CoV‐2 following cell exposure to emvododstat.…”
Section: Introductionmentioning
confidence: 99%